Analysis Application of Social Media Communication Effectiveness in Maritime English - Muhammad Natsir; Bahagia Saragih; Anggraini Thesisia Saragih (Randwick International of Education and Linguistics Science Journal, 2023)
The wonder of the nearness of social media and mass media may be a result of the exceptional improvement of data and communication innovation. With a assortment of administrations that can be utilized, social media has changed the way we communicate in society. The nearness of social media indeed has an affect on the way we communicate in all areas, such as showcasing communication, political communication, and communication in learning frameworks. This is certainly interesting to study by analyzing the effectiveness of social media in maritime English. Through data collection techniques through literal studies (library studies). The literature study was conducted by collecting secondary data related to topics and problems related to the use of Analysis of the Application of Effectiveness of Social Media Communication in Maritime English. By analyzing data sources regarding social media, the use of social and mass media as a means of developing communication in maritime English. With the aim of looking at the effectiveness of social and mass media in maritime English communication.